Anatomical and Physiological Features of the Skin Structure in Childhood (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The skin of a child differs in its structure from the skin of an adult. First of all, it makes up 1/12 of the total body weight, and on this basis it is surpassed only by the striated muscle and bone systems. When the body interacts with the external environment, it is the first line of defense against harmful influences. In this regard, any damage to the skin is a significant danger for the baby. The skin, regardless of the body area, consists of three main layers: the epidermis — the thinnest outer layer; the dermis, or middle layer, and subcutaneous fat. The epidermis constantly regenerates and contains melanocytes.